The Meaning of Work in a Sustainable Society - Bellamy Foster, John (Revista Internacional de Salarios Dignos, 2020)
The nature and meaning of work, as it pertains to a future society, has deeply divided ecological, socialist, utopian, and Romantic thinkers since the Industrial Revolution. Some radical theorists have seen a more just society as merely requiring the rationalisation of present-day work relations, accompanied by increased leisure time and more equitable distribution.